2010
DOI: 10.1007/s11105-010-0179-z
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Cucumis sativus Expressing the Hepatitis B Surface Antigen

Abstract: A DNA fragment encoding the hepatitis B virus surface antigen was amplified from a positive blood (hepatitis B) sample and introduced into the pET 32c prokaryotic expression vector. The gene encoding the HBV surface protein antigen was introduced into pCAMBIA 3300, and immobilized into Agrobacterium tumefaciens strain LBA4404. Cotyledonary leaf sections of Cucumis sativus (cucumber) cv 'Swarnamukhi' were cocultivated with Agrobacterium harboring the binary vector pCAMBIA 3300 carrying the HBV surface antigen g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In the first position was sanggenol compound O and in the second position was cucumerin A, contained in the plant Cucumis sativum, commonly referred to as cucumbers in Indonesia. Research has shown that cucumber is an ideal plant for HBsAg expression to be used as an oral vaccine [7]. In third place was yuehchukene compound, and in the fourth place was palmarumycin CP1 compounds derived from the Jatropha curcas plant in Java (known as Jarak).…”
Section: Virtual Screening Using Autodock Vinamentioning
confidence: 99%
“…In the first position was sanggenol compound O and in the second position was cucumerin A, contained in the plant Cucumis sativum, commonly referred to as cucumbers in Indonesia. Research has shown that cucumber is an ideal plant for HBsAg expression to be used as an oral vaccine [7]. In third place was yuehchukene compound, and in the fourth place was palmarumycin CP1 compounds derived from the Jatropha curcas plant in Java (known as Jarak).…”
Section: Virtual Screening Using Autodock Vinamentioning
confidence: 99%
“…Many of HBsAg expression systems are still undergoing the process of development and optimisation and new plant species are being tested as possible expression systems. The most recent experiments include cucumber (Unni and Soniya, 2010), sandalwood embryogenic cell suspension cultures (Shekhawat et al, 2010), maize (Hayden et al, 2012;Hayden et al, 2015;Shah et al, 2015) and lettuce (Pniewski et al, 2011), as well as the most recent progress in using potato as host system (Rukavtsova et al, 2015). Even though the first effective parental hepatitis B vaccine by yeast has been developed more than 20 years ago, the vaccine still isn't accessible, effective or is costprohibitive for a lot of world's population, especially for areas that need it the most.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Similarly, mammalian cell cultures are expensive, hindering production of large quantities of vaccines. The development of various plant expression systems has enabled the expression of foreign antigens in plant tissue as edible vaccine vehicles (Haq et al 1995 ; Du et al 2005 ; El Adab et al 2007 ; Ko et al 2009 ; Sim et al 2009 ; Unni and Soniya 2010 ; Cui et al 2011 ; Guo et al 2012 ). Plant-based edible vaccines offer advantages of longer shelf-life, stability at room temperature without loss of immunogenicity, and reduced production costs (Streatfield et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%